EFFECTIVENESS OF PROGRESSIVE MOBILIZATION LEVEL I AND II ON HEMODYNAMIC STATUS AND DECUBITUS ULCER RISK IN CRITICALLY ILL PATIENTS - Ni Wayan Rahayu Ningtyas; RR Sri Endang Pujiastuti; Nina Indriyawati (Belitung Raya Foundation, Indonesia, 2017)
Background: Patient immobility remains to be one of the primary causes of pressure ulcers. Therefore, mobilization is necessity for patients being treated in the intensive care unit. However, the occurrence of pressure ulcers is dependent on not only the mobilization but also the bed itself and the type of mattress. This study used the same mattress and bed and compared the effectiveness of progressive mobilization with regular mobilization. Objective: This study aims to examine the effectiveness of progressive mobilization level I and II on hemodynamic status and decubitus ulcer risk in critically ill patients. Methods: This was a quasi-experimental study using repeated measure design. There were 40 respondents selected using purposive sampling, which 20 respondents assigned in each group. A Braden scale was used to measure the risk of decubitus ulcer. Paired t-test and repeated measures ANOVA were performed for data analysis. Results: Paired t-test showed that there was a significant difference of systolic pressure, diastolic pressure, MAP, heart rate, and Braden score after given intervention with p-value <0.05. However, repeated ANOVA test showed that diastolic pressure had p-value >0.05, thus could not be continued to post-hoc test. The progressive mobilization of level I and II in critical patients can stabilize systolic pressure (52.46%), stabilize MAP (58.43%), stabilize heart rate (68.99%), and reduce the risk of decubitus (55.03%) for 7 days of recurrent intervention. Conclusion: The progressive mobilization of level I and II can reduce the risk of decubitus and stabilize the patient's hemodynamic status in critical patients.